Big Bang nucleosynthesis and physics beyond the Standard Model - Sarkar, S (1996)
The Hubble expansion of galaxies, the $2.73\dK$ blackbody radiation background and the cosmic abundances of the light elements argue for a hot, dense origin of the universe --- the standard Big Bang cosmology --- and enable its evolution to be traced back fairly reliably to the nucleosynthesis era when the temperature was of $\Or(1)$ MeV corresponding to an expansion age of $\Or(1)$ sec. All particles, known and hypothetical, would have been created at higher temperatures in the early universe and analyses of their possible effects on the abundances of the synthesized elements enable many interesting constraints to be obtained on particle properties. These arguments have usefully complemented laboratory experiments in guiding attempts to extend physics beyond the Standard $SU(3)_{\c}{\otimes}SU(2)_{Ł}{\otimes}U(1)_{Y}$ Model, incorporating ideas such as supersymmetry, compositeness and unification. We first present a pedagogical account of relativistic cosmology and primordial nucleosynthesis, discussing both theoretical and observational aspects, and then proceed to examine such constraints in detail, in particular those pertaining to new massless particles and massive unstable particles. Finally, in a section aimed at particle physicists, we illustrate applications of such constraints to models of new physics.